2021
DOI: 10.3390/su132413794
|View full text |Cite
|
Sign up to set email alerts
|

Rural Transformation and Labor Market Outcomes among Rural Youths in Nigeria

Abstract: In Nigeria, unemployment in rural areas translates to economic problems, such as high levels of rural–urban migration. Interventions aimed at promoting rural transformation and development are designed to generate employment by promoting the growth of sectors such as manufacturing and services in rural areas. In this study, the General Household Survey (GHS) panel data for the post-planting and post-harvest periods of the 2011/2012 and 2015/2016 cropping seasons for Nigeria was used to investigate developments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(44 reference statements)
0
5
0
1
Order By: Relevance
“…The mean annual income of the respondents was 348,043.26 Naira. This indicated that the youths are low income earners and it has negative implication on their ability to invest in livestock production business (Rufai et al, 2021). More than half of the respondents (51.99%) had a livestock business experience of less than 10 years while 48.01% of the respondents had more than 10 years' experience in the livestock business.…”
Section: A Personal Characteristics Of the Respondentsmentioning
confidence: 98%
“…The mean annual income of the respondents was 348,043.26 Naira. This indicated that the youths are low income earners and it has negative implication on their ability to invest in livestock production business (Rufai et al, 2021). More than half of the respondents (51.99%) had a livestock business experience of less than 10 years while 48.01% of the respondents had more than 10 years' experience in the livestock business.…”
Section: A Personal Characteristics Of the Respondentsmentioning
confidence: 98%
“…Based on the connotation characteristics of rural transformation development, this paper refers to the research results of the rural transformation development evaluation index system. In this paper, the evaluation index system of the rural transformation development level of The Yangtze River Economic Belt was constructed from the dimension of "population-land-industry" [33,34] (Table 1). 1 Population development transformation.…”
Section: Index System and Data Collection 221 Index Systemmentioning
confidence: 99%
“…However, the extent to which youth contribute to households' welfare has gained little or no research attention despite a huge literature on rural youths (Adeyanju et al, 2021;Akrong & Kotu et al, 2022;Arslan et al, 2021a;Arslan et al, 2021a;Barsoum et al, 2017;Fasakin et al, 2022;Fawole et al, 2019;Ibrahim et al, 2021;Ng'atigwa et al, 2020;Osabohien et al, 2020;Osabohien et al, 2021;Rufai et al, 2021). Recent studies on rural households' welfare focus on the level of welfare (Donath et al, 2021;Delesalle, 2021).…”
Section: Introductionmentioning
confidence: 99%